2019
DOI: 10.1097/md.0000000000014341
|View full text |Cite
|
Sign up to set email alerts
|

Metallic artifact reduction by evaluation of the additional value of iterative reconstruction algorithms in hip prosthesis computed tomography imaging

Abstract: To evaluate iterative metal artifact reduction (iMAR) technique in images data of hip prosthesis on computed tomography (CT) and the added value of advanced modeled iterative reconstruction (ADMIRE) compared with standard filtered back projection (FBP). Twenty-eight patients addressed to CT examinations for hip prosthesis were included prospectively. Images were reconstructed with iMAR algorithm in addition to FBP and ADMIRE techniques. Measuring image noise assessed objective image quality and atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…We attribute the improved image quality achieved with MBIRþMAR to the incorporation of MBIR settings such as the focus size, detector size, and voxel size, which would improve the spatial resolution. In previous analyses, Wellenberg et al 39 and Neroladaki et al 40 reported that MBIRþMAR significantly reduced orthopedic metal artifacts on pelvic CT images produced by other vendors., Although the results of those studies were consistent with our findings, the AJNR Am J Neuroradiol : 2020 www.ajnr.org methods differed from ours in that either phantoms or small numbers of large orthopedic metal implants were used. A previous phantom study observed that the metal artifacts increased and the CT image accuracy decreased as the number of metal implants in the oral cavity increased.…”
Section: Discussionmentioning
confidence: 96%
“…We attribute the improved image quality achieved with MBIRþMAR to the incorporation of MBIR settings such as the focus size, detector size, and voxel size, which would improve the spatial resolution. In previous analyses, Wellenberg et al 39 and Neroladaki et al 40 reported that MBIRþMAR significantly reduced orthopedic metal artifacts on pelvic CT images produced by other vendors., Although the results of those studies were consistent with our findings, the AJNR Am J Neuroradiol : 2020 www.ajnr.org methods differed from ours in that either phantoms or small numbers of large orthopedic metal implants were used. A previous phantom study observed that the metal artifacts increased and the CT image accuracy decreased as the number of metal implants in the oral cavity increased.…”
Section: Discussionmentioning
confidence: 96%
“…As quantitative indices for dark bands, the area on the image with CT values lower than the threshold and the mean CT value of the area are frequently used. [ 2 , 6 , 7 , 18 ] Fine streak artifacts were evaluated objectively by using SD and artificial index, which was calculated using SD by placing an ROI within the fine streak artifacts [ 8 , 19 , 20 ] ; however, the SD contained the effect of image noise and did not seem to reflect only metal artifacts. To remove the effect of image noise, it seems to be necessary to subtract SD of CT values within the ROI in the phantom without the metal implant from that in the phantom with the metal implant.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] In comparing MARs with MBIR, Angeliki et al showed that iterative MAR allowed significant reduction of metal artifacts, including dark streaks, as compared to advanced modeled iterative reconstruction (ADMIRE; Siemens). [ 7 ] Yasaka et al reported that single-energy MAR (Canon Medical Systems, Ohtawara, Japan) significantly reduced metal artifacts, including dark streaks, as compared to a forward-projected MBIR solution (Canon Medical Systems). [ 24 ] In our study, MAR showed significant efficacy in reducing dark bands as compared to other methods of reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although doctors make clinical efforts to manually collect such artifacts, this is a labor-intensive and time-consuming task. Many researchers have studied image filtering or reconstruction methods [2], [4]- [7], but metal artifact reduction (MAR) remains a challenging problem [8]- [10], and no standard algorithm for strong, complex artifacts with missing pixels derived from multiple metal objects has yet been established.…”
Section: Introductionmentioning
confidence: 99%